The Doubly Labeled Water Method Produces Highly Reproducible Longitudinal Results in Nutrition Studies. Issue 5 (12th February 2014) - Wong, William W.; Roberts, Susan B.; Racette, Susan B.; Das, Sai Krupa; Redman, Leanne M.; Rochon, James; Bhapkar, Manjushri V.; Clarke, Lucinda L.; Kraus, William E.
Abstract: The doubly labeled water (DLW) method is considered the reference method for the measurement of energy expenditure under free-living conditions. However, the reproducibility of the DLW method in longitudinal studies is not well documented. This study was designed to evaluate the longitudinal reproducibility of the DLW method using 2 protocols developed and implemented in a multicenter clinical trial—the Comprehensive Assessment of Long-term Effects of Reducing Intake of Energy (CALERIE). To document the longitudinal reproducibility of the DLW method, 2 protocols, 1 based on repeated analysis of dose dilutions over the course of the clinical trial (dose-dilution protocol) and 1 based on repeated but blinded analysis of randomly selected DLW studies (test-retest protocol), were carried out. The dose-dilution protocol showed that the theoretical fractional turnover rates for 2 H and 18 O and the difference between the 2 fractional turnover rates were reproducible to within 1% and 5%, respectively, over 4.5 y. The Bland-Altman pair-wise comparisons of the results generated from 50 test-retest DLW studies showed that the fractional turnover rates and isotope dilution spaces for 2 H and 18 O, and total energy expenditure, were highly reproducible over 2.4 y. Our results show that the DLW method is reproducible in longitudinal studies and confirm the validity of this method to measure energy expenditure, define energy intake prescriptions, and monitor adherence and body composition changes over the period of 2.5–4.4 y. The 2 protocols can be adopted by other laboratories to document the longitudinal reproducibility of their measurements to ensure the long-term outcomes of interest are meaningful biologically. This trial was registered at clinicaltrials.gov as NCT00427193.